Two-dimensional materials for electrochromic applications. Issue 5 (September 2021) - Li, Jianmin; Zhuang, Yanling; Chen, Jianmei; Li, Bingxiang; Wang, Longlu; Liu, Shujuan; Zhao, Qiang
Highlights: Typical structure and evaluation of electrochromic devices. Recent developments in electrochromic active electrode using 2D materials. Summarizing the advanced 2D materials for flexible transparent conducting layer. Remaining challenges and future research directions of 2D materials towards electrochromic applications. Abstract: Electrochromic devices (ECDs), which generate reversible color changes by the electrochemical reaction, have shown tremendous promise in the field of smart windows, displays, and the future wearable electronics, due to their benefits of simple structure, low power consumption, as well as multi-colors. In the past decade, two-dimensional (2D) materials, such as graphene, metal oxides/carbides/nitrides/dichalcogenides, conductive polymer, metal-organic frameworks, and covalent organic frameworks, that represent good mechanical properties, superior electrochemical activity, fast charge transfer speed, and other unique physical properties, have been widely applied in the ECDs and induced great improvement of the field. As a result, some long-playing issues of ECDs are in prospect to be settled by using 2D materials. This review starts from summarizing the evaluation standard of ECDs, followed by highlighting the most up-to-date exciting results regarding the design and application of 2D materials for the electrochromic layer. Meanwhile, the superior effects of graphene and MXenes for advanced flexible transparent conducting layer are discussed in detail. At last, the remaining challenges and possible research directions for the future of this field are also proposed. Hopefully, the review may shed light on the main trends for developing high-performance ECDs, and provide referencing value for other researchers, to and finally boost the practical applications of ECDs. Graphical abstract: Image, graphical abstract